Increasing the Operational Stability of Vortex Frequency Transducers in Contact-Conductometric Vortex Flowmeters for Wastewater from Pulp and Paper Production - Lur’e, M. S.; Lur’e, O. M.; Frolov, A. S. (Measurement techniques, 2023)
We examine issues of increasing the stability of the operation of submersible vortex frequency transducers in contact-conductometric vortex flowmeters for wastewater from pulp and paper production. Due to their design, converters of this type are subject to periodic breakdowns because of the oscillations of the sensitive element at a certain critical flow rate. The stability of the operation of these converters is analyzed using the theory of nonlinear impulse systems. It has been established that the flow measurement error increases due to the loss of the output signal flow meter at critical flow. It is shown that the critical flow rate is due to the added mass of the liquid, oscillating together with the sensitive element of the vortex frequency transducer of the flowmeters. The added liquid mass is determined from the frequency characteristics of the sensitive elements of the vortex frequency transducer by using numerical simulation and experimental studies on a special test stand. By using these results the amplitude–frequency characteristics of the sensitive elements are obtained. From comparative analysis of simulation and experimental characteristics we established the additional energy losses during oscillations of the sensitive element. Based on the results of this investigation, requirements for the design of vortex frequency transducers have been formulated regarding choice of mechanical parameters of the flexible electrode, eliminating measurement errors and providing stable operation of the device in the entire range of flow measurements. The results are relevant for organizations involved in the development and the introduction of flow measuring equipment and wastewater monitoring.